Respuesta :

Let's assume the opposite is the case. So let's assume that a = b is true. If so, then f(a) and f(b) would be the same output. This is because we can replace 'b' with 'a', or vice versa. In other words, f(a) = f(b) would be true. But this contradicts the original inequality that f(b) < f(a)

So that is why 'a' cannot equal b. We don't know if a > b or if a < b (unless we are told if the function is strictly decreasing or increasing on the interval from x = a to x = b), so we just leave it as [tex]a \ne b[/tex]